Learning Media Based on Augmented Reality on Cube Material Class IX Junior High School - Retni Paradesa; Suzana Paranita; Dwi Nisa oktarisa (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
This research aims to produce augmented reality-based learning media on class IX SMP cube material that is valid, practical, and has a potential effect on the learning outcomes of class IX students at Nurul Amal Middle School, Palembang. This type of research is development using the ADDIE model which consists of the Analyze, Design, Development, Implementation and Evaluation stages. The data collection techniques used were validation sheets, questionnaires, interviews and tests. Based on the results of the research, it was found that augmented reality-based learning media in class IX SMP cube material was declared valid by the validator, it was practical for students in the one-to-one trial stage, small group trials and field trials, and had practicality for learning outcomes of students after using the learning media developed.